2015
DOI: 10.3109/09513590.2015.1006617
|View full text |Cite
|
Sign up to set email alerts
|

Dienogest. A possible conservative approach in bladder endometriosis. Results of a pilot study

Abstract: Deep endometriosis involvement of the bladder is uncommon but it is symptomatic in most of the cases. Although laparoscopic excision is very effective, some patients with no pregnancy desire require a medical approach. We performed a pilot study on the effect of a new progestin dienogest on bladder endometriosis. Six patients were treated for 12 months with dienogest 2 mg/daily. Pain, urinary symptoms, quality of life, nodule volume and side effects were recorded. During treatment, symptoms improved very quick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…Agarwal et al [98] observed relief of catamenial dysuria and hematuria and a >50% reduction in lesion size in a woman treated with dienogest for 16 mo for a 3-cm endometriotic bladder nodule. Angioni et al [99] used the same dienogest dose for 1 yr in six women who requested a medical approach for BE. Their pain and urinary symptoms improved very quickly and the nodule decreased remarkably in size in all patients [99].…”
Section: Medical Therapies For the Treatment Of Bementioning
confidence: 99%
See 1 more Smart Citation
“…Agarwal et al [98] observed relief of catamenial dysuria and hematuria and a >50% reduction in lesion size in a woman treated with dienogest for 16 mo for a 3-cm endometriotic bladder nodule. Angioni et al [99] used the same dienogest dose for 1 yr in six women who requested a medical approach for BE. Their pain and urinary symptoms improved very quickly and the nodule decreased remarkably in size in all patients [99].…”
Section: Medical Therapies For the Treatment Of Bementioning
confidence: 99%
“…Angioni et al [99] used the same dienogest dose for 1 yr in six women who requested a medical approach for BE. Their pain and urinary symptoms improved very quickly and the nodule decreased remarkably in size in all patients [99]. Leone Roberti Maggiore et al [39] used dienogest 2 mg/d to treat a 34-yr-old nulliparous woman with urgency and stress urinary incontinence associated with BE who refused surgery.…”
Section: Medical Therapies For the Treatment Of Bementioning
confidence: 99%
“…In animal studies, dienogest demonstrated anti-proliferative, anti-inflammatory and anti-angiogenic effects towards endometriosis tissue [12]. In clinical trials, dienogest has been reported to be successful in reducing both the symptoms and the size of rectosigmoid and bladder endometriosis after 10 to 11 months of usage [14]. Until now, no literature has described the success of dienogest in treating PUE.…”
Section: Discussionmentioning
confidence: 97%
“…Women in DNG group reported a significant amelioration compared to control group in pain symptoms and QoL at the first follow-up, and in Another field of application of DNG treatment is bladder endometriosis. A recent pilot study [35] on six patients treated for 12 months with DNG 2 mg/d showed an improvement of pain symptoms in all patients. In particular, urinary symptoms disappeared and at transvaginal ultrasound a significant decrease of bladder nodule size at 3-and 12-months evaluation was described.…”
Section: Norethisterone Acetatementioning
confidence: 90%